Basic Sector Analysis and Development Strategy of Regional Economic Potential in Kulon Progo District 2013-2017 - Mulya Isabhandia, Yonanda; Setiartiti, Lilies (Journal of Economics Research and Social Sciences, 2021)
The research carried out in Kulon Progo Regency aims to analyze the economic potential that will exist to develop strategies that can be used to develop the economy in Kulon Progo Regency. This study uses data from 2013 to 2017 obtained from the Central Statistics Agency of Kulon Progo Regency and Yogyakarta Special Region. This study uses several analytical tools, namely Statistical Location Quotient (SLQ), Dynamic Location Quotient (DLQ), Shift Share Analysis, Klassen Typology Analysis, and the SWOT analysis approach. Based on the combined analysis of SLQ and DLQ, there are three sectors: the mining and quarrying sector, wholesale trade and retail, car and motorcycle repair, government administration, defense, and social security. These sectors are the crucial sectors at present and will remain the base sectors in the future.